Numerical Study of a Thermally Stressed State of a Rod. (2nd June 2019) - Kudaykulov, Anarbay; Arinov, Erkin; Ispulov, Nurlybek; Qadir, Abdul; Begaliyeva, Kalamkas
Abstract : This paper considers a new method based on the law of energy conservation for the study of thermo-stress-strain state of a rod of limited length with simultaneous presence of local heat fluxes, heat exchanges, and thermal insulation. The method allows determining the field of temperature distribution and the three components of deformations and stresses, as well as the magnitude of the rod elongation and the resulting axial force with an accuracy of satisfying the energy conservation laws. For specific initial data, all the sought-for ones are determined numerically with high accuracy. We found that all solutions satisfy the laws of energy conservation.